Lebah Madu Sebagai Motif Pada Karya Seni Kulit Dua Dimensi - Paulina Wati Tumeang; Ferawati (VisArt: Jurnal Seni Rupa dan Design, 2025)
The creation of this two-dimensional leather craft work takes the form of a wall decoration inspired by the object of the honeybee, entitled “Hard Work Leads to Results.” This artwork depicts the activity of bees in collecting food in the form of pollen from flowers, which is then processed into sweet honey. The bees’ activity is interpreted as a symbol of human perseverance and hard work in living life and carrying out one’s occupation, while the sweetness of honey represents the results or rewards obtained from such hard work, such as enjoying the outcomes of effort and the income earned. In its creation process, this two-dimensional leather craft work employs three stages of creation: the exploration stage, which involves searching for and developing sources of ideas; the design stage, which produces sketches and design concepts; and the realization stage, which transforms the concept into a finished leather artwork. The final work consists of a single piece made from vegetable-tanned leather, measuring 54 cm in width and 74 cm in height. The technique applied is the embossed carving technique (tatah timbul), which serves to highlight the motifs and strengthen the visual character of the leather craft. The final finishing stage uses glazing paint to create a more vivid visual impression, emphasize details, and enhance the overall aesthetic value of the artwork